Optimizing the Use of Google Classroom as an Integrated Learning Management System in Teaching Writing - Aziza Restu Febrianto (English Education Department - Universitas Nasional Karangturi, 2021)
Google Classroom (GC), as one of the learning management systems (LMS), has been widely used by many educators and researched in many studies for its efficacy in assisting both teachers and students in learning a second language. This article presents a report of exploratory research about the possibilities of getting the most out of GC for educators to provide effective scaffoldings that can help their students achieve the goals of learning in writing. Referring to the concept of Zone Proximal Development (ZPD), the teaching and learning cycles (TLC), and the theories of distance learning, this article also attempts to display a model of ideal scaffoldings relevant for teaching writing in an online environment. Besides, through observations and investigations on a range of tools and materials on the internet and those discussed in different studies, this research reveals various types of potential applications that can be integrated with GC to make the lessons of writing more interactive and engaging. By reviewing other studies on the use of GC, this study highlights several technical issues and challenges to face when using the platform, particularly in teaching writing. For this reason, finding out appropriate ways and strategies on how to deal with the issues needs to be seriously considered so that the scaffoldings that have been designed can work as expected for effective online teaching and learning processes.